The Relationship Between Motivation And Medication Adherence In Hypertensive Patients At Puskesmas Susua, Susua District, South Nias Regency - Siburian, Christine Handayani; Naibaho, Eka Nugraha V; Silaban , Nataria Yanti (SEAN Institute, 2023)
Hypertension or high blood disease is a condition in which there is an increase in blood pressure above the normal threshold. The desire of hypertensive patients to recover from the disease is very necessary for motivation in the patient. The purpose of motivation is to move or arouse individuals to arise the will to recover from illness. Recovery from an illness requires patient compliance in taking medicine. Adherence to taking medication is a behavior of hypertensive patients in taking anthypertension drugs in accordance with their recommendations. The purpose of this study was to determine the relationship between motivation and medication adherence in hypertensive patients at Susua Health Center, Susua District, South Nias Regency. The research design used Cross Sectional. The sample was 40 respondents of hypertensive patients at the Susua Health Center, Susua District, South Nias Regency with the sampling technique being a purposive sampling technique. The study data was collected using motivation questionnaires and Morisky Medication Adherence Sacle (MMAS) questionnaires. The data were analyzed with the Spearman Rho correlation test. The results found a relationship between motivation and adherence to taking medication in hypertensive patients (p = 0.00, r = 0.742). The results of this study can recommend that the need for nursing actions that can increase motivation so that patient medication adherence can increase in hypertensive patients.